The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1097/qai.0b013e3181eda955
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Treatment Trial: Single Versus 7-Day Dose of Metronidazole for The Treatment of Trichomonas Vaginalis Among HIV-Infected Women

Abstract: Objective To determine if the metronidazole (MTZ) 2 gm single dose (recommended) is as effective as the 7 day 500 mg BID dose (alternative) for treatment of Trichomonas vaginalis (TV) among HIV+ women. Methods Phase IV randomized clinical trial; HIV+ women with culture confirmed TV were randomized to treatment arm: MTZ 2 gm single dose or MTZ 500 mg BID 7 day dose. All women were given 2 gm MTZ doses to deliver to their sex partners. Women were re-cultured for TV at a test-of-cure (TOC) visit occurring 6-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 36 publications
3
59
2
Order By: Relevance
“…17 The second cohort, cohort B, consisted of 125 HIV-positive, TV-positive women recruited from HIV outpatient clinics in Houston, TX; Jackson, MS; and New Orleans, LA; between May 2006 and July 2009 to participate in a randomized treatment trial that sought to determine whether a 2-g single dose of metronidazole (MTZ) was as effective as a 7-day 500-mg twice-a-day dose for treatment of TV in HIV-positive women. 35 To be eligible for either study, women were required to provide consent, be HIV positive, be 18 years or older, and have their positive test result for TV confirmed by InPouch culture technique (InPouch; Biomed Diagnostics, White City, OR). 35 Exclusion criteria for both cohorts were as follows: pregnancy, incarceration, alcoholism, taking disulfiram, having received MTZ within the previous 14 days (to avoid persistent TV), or having a medical contraindications to MTZ.…”
Section: Participantsmentioning
confidence: 99%
“…17 The second cohort, cohort B, consisted of 125 HIV-positive, TV-positive women recruited from HIV outpatient clinics in Houston, TX; Jackson, MS; and New Orleans, LA; between May 2006 and July 2009 to participate in a randomized treatment trial that sought to determine whether a 2-g single dose of metronidazole (MTZ) was as effective as a 7-day 500-mg twice-a-day dose for treatment of TV in HIV-positive women. 35 To be eligible for either study, women were required to provide consent, be HIV positive, be 18 years or older, and have their positive test result for TV confirmed by InPouch culture technique (InPouch; Biomed Diagnostics, White City, OR). 35 Exclusion criteria for both cohorts were as follows: pregnancy, incarceration, alcoholism, taking disulfiram, having received MTZ within the previous 14 days (to avoid persistent TV), or having a medical contraindications to MTZ.…”
Section: Participantsmentioning
confidence: 99%
“…10 Kissinger et al studied effect of single versus 7 days dose of metronidazole for treatment of Trichomonas vaginalis among 270 HIV positive patients. 11 They found 7 days treatment is more effective in HIV positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, treatment failure may be an important cause of recurrence. Although several studies indicate a single dose of oral metronidazole as the �rst alternative for treatment, Kissinger et al [58], in a randomized clinical study on HIV-infected women, showed that oral metronidazole for seven days was more effective in eradicating T. vaginalis.…”
Section: Discussionmentioning
confidence: 99%